2012
DOI: 10.1038/jhg.2012.101
|View full text |Cite
|
Sign up to set email alerts
|

Associations of variations in the MRF2/ARID5B gene with susceptibility to type 2 diabetes in the Japanese population

Abstract: Modulator recognition factor-2 (Mrf2/AT-rich interaction domain (Arid)5b) has been revealed to be involved in pathogenesis of atherosclerosis and adipogenesis. Single-nucleotide polymorphisms (SNPs) in the MRF2/ARID5B gene are associated with coronary artery disease (CAD) and has been proposed as a candidate gene for type 2 diabetes (T2D). The study was aimed to determine whether any of the four MRF2/ARID5B SNPs (rs2893880, rs10740055, rs7087507 and rs10761600) associated with susceptibility to CAD are also as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 35 publications
(46 reference statements)
1
14
1
Order By: Relevance
“…The four variants were also associated with higher HbA1c and FPG levels. [11] In the present study, participants who harbored the MRF2/ARID5B rs10740055AA genotype had a higher incidence of T2DM, and the risk of T2DM was also increased in subjects harboring the T allele of rs10761600, consistent with the results of the previous study. The rs10740055 and rs10761600 SNPs thus appear to be common loci for T2DM susceptibility among Asian populations.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The four variants were also associated with higher HbA1c and FPG levels. [11] In the present study, participants who harbored the MRF2/ARID5B rs10740055AA genotype had a higher incidence of T2DM, and the risk of T2DM was also increased in subjects harboring the T allele of rs10761600, consistent with the results of the previous study. The rs10740055 and rs10761600 SNPs thus appear to be common loci for T2DM susceptibility among Asian populations.…”
Section: Discussionsupporting
confidence: 92%
“…[1112] However, the relationships between these four SNPs and T2DM have only been reported in a Japanese population.…”
Section: Introductionmentioning
confidence: 99%
“…Regulation of EHD3 plays a role in a molecular pathway related to heart failure (Gudmundsson et al, 2012). ARID5B is involved in pathogenesis of atherosclerosis and adipogenesis (Wang et al, 2012). ABCC6 is associated with transport of molecules across membranes and is associated with premature atherosclerosis (Trip et al, 2002), and CUL7 plays a role in vascular morphogenesis (Arai et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the expression of multiple adipogenic genes was inhibited following transient transfection of siRNA targeting ARID5B in 3T3-L1 cells (14). Since a role of ARID5B in the regulation of metabolism has been suggested (11)(12)(13), we investigated the potential involvement of ARID5B and AMP-activated protein kinase (AMPK) in the metabolism of cardiac myocytes.…”
Section: Arid5b (At-rich Interaction Domain-containingmentioning
confidence: 99%
“…Important roles of ARID5B in growth, immune, and sexual development have been suggested (10). While the role of ARID5B in cancer is still elusive, previous studies suggested that genetic variations in the ARID5B gene are associated with susceptibility to coronary atherosclerosis or type 2 diabetes in Japanese populations (11,12).…”
Section: Arid5b (At-rich Interaction Domain-containingmentioning
confidence: 99%